Systematic Review and Meta-Analysis of the Quality of Life in Iranian Elderly People Using LEIPAD Questionnaire - Masoumeh Erfani Khanghahi; Farbod Ebadi Fard Azar (Tehran University of Medical Sciences, 2018)
Background and Aim: With the increasing number of elderly people, quality of their life is important . The purpose of this study was systematic review and meta-analysis of the quality of life in elderly Iranians using LEIPAD questionnaire. Materials and Methods: Required information  was searched on internet using terms such as quality of life, LEIPAD, elderly, older people, aging, older Age from databases of PubMed Scopus, Elsevier, Google Scholar, and Persian equivalents of SID, Medlib, IranDoc, MagIran, IranMedex from 2000 to 2015, has been searched. The criteria for entering the study were: published articles in Persian and English languages, and mentioning at least the total score of quality of life Meta-analysis software: CMA: 2 was used. Results: From three hundred and forty eight articles found, 8 articles finally entered the study. In general, the results showed that the overall average quality of life of older people was [52.2-64.7 95% CI] 10.1 ± 58.5. The average overall quality of life of the elderly in the community was 15.5 ± 57.6. The average overall quality of life for the elderly in nursing homes was 29.7 ± 60.1. Aspects of self-care and mental dimension had higher scores. sexual functioning , depression and anxiety scores were lower. Conclusion: The results showed that quality of life in elderly Iranians is average, therefore planning and effective interventions are needed. More attention to aspects of sexual functioning and depression and anxiety in the planning and intervention is necessary